2010
DOI: 10.1155/2011/672136
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation of Yukmijihwang-tang: Assessment of Acute and Subchronic Toxicity in Rats

Abstract: Yukmijihwang-tang (YMJ; Liu wei di huang tang (China), Rokumigan (Japan)) has been used in the treatment of diseases including renal disorder, cognitive vitality, and diabetes mellitus. However, there is very little information regarding the toxicity of YMJ to give an assurance of safety for clinical treatment. To provide safety information for YMJ, we evaluated its acute and sub-chronic toxicity in rats. The single-dose toxicity of YMJ was examined using Sprague-Dawley rats. Rats were treated with YMJ extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Gross postmortem examinations were performed after an overdose of anesthetic as described previously [ 11 ]. Absolute organ weights were measured and relative organ weights (organ-to-body weight ratios) were calculated for the following: brain, pituitary gland, adrenal gland, liver, spleen, kidneys, heart, thymus, lung, salivary gland, thyroids, testes, ovaries, epididymides, seminal vesicle, prostate, and uterus.…”
Section: Methodsmentioning
confidence: 99%
“…Gross postmortem examinations were performed after an overdose of anesthetic as described previously [ 11 ]. Absolute organ weights were measured and relative organ weights (organ-to-body weight ratios) were calculated for the following: brain, pituitary gland, adrenal gland, liver, spleen, kidneys, heart, thymus, lung, salivary gland, thyroids, testes, ovaries, epididymides, seminal vesicle, prostate, and uterus.…”
Section: Methodsmentioning
confidence: 99%
“…In the pharmacokinetic aspect, the metabolism rate in small animals including mouse and rat is faster than in humans [ 25 ]. As we previously reported [ 13 ], the equivalent dose of YMJ in rats converted from its single dose in humans was 1,329 mg according to van Miert [ 26 ], which is a value less than the NOAEL (2000 mg/kg in rats). The single administration dose of YMJ in human is 46.875 g dried herb [ 1 ], which is equivalent to 12.656 g of the extract (yield = 27.0% of the raw material).…”
Section: Discussionmentioning
confidence: 96%
“…Previously, we reported on the acute and subchronic toxicity as well as genotoxicity of YMJ in an animal model. We found that YMJ had no acute and subchronic toxicity or genotoxicity and its no-observed-adverse-effect-level (NOAEL) is 2000 mg/kg/day [ 13 , 14 ]. However, there has been no report on the subacute toxicity of YMJ.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional medicines, including Chinese prescriptions, have attracted much attention due to their extensive and unique biological activities without toxicity and/or side effects [4]. Hachimi-jio-gan has been long and widely used to treat several chronic diseases, including nephritis, infertility diabetes, and vegetative ataxia [5], although scientific evidence supporting the pharmacological basis for its therapeutic effects has not yet been well established.…”
Section: Introductionmentioning
confidence: 99%